Advanced Techniques for Transit Priority at Roundabouts utilizing Signal Metering - Halawani, Ahmed T. M. (Engineering, Technology & Applied Science Research, 2025)
Transit priority strategies frequently focus on conventional Transit Signal Priority (TSP) at intersections, overlooking the distinct operational characteristics of roundabouts, including signalized, metered, and yield-based control methods. This study introduces a new approach, Transit Metering Signal Priority (TMSP), which uses metering signals to provide Public Transport Vehicles (PTVs) preference at roundabouts. A distinguishing feature of TMSP is its compatibility with the existing yield or metering control strategies employed by roundabouts, allowing them to maintain these methods without the full signalization of all approaches for priority allocation to PTVs the latter involves. The efficacy of the proposed TMSP model is assessed through numerical experiments, with yield control (no priority) serving as the baseline. Comparisons are drawn between conventional TSP and TMSP scenarios under varying congestion levels. The findings suggest that the proposed TMSP logic can lead to a reduction in bus delays by 2 sec to 16.6 sec, with minimal impact on general traffic, while also decreasing travel time variability by up to 19 sec (standard deviation). In comparison to TSP, TMSP exhibits clear advantages for public transportation by reducing delays and providing more stable travel times, while minimizing disruptions to the general traffic flow. The implementation of the TMSP method enhances the performance and reliability of public transport services, contributing to the development of more resilient and sustainable urban mobility systems.